The institute of probation and practicality of its use in Ukraine - Ovdienko, G.V. (ХНУ ім. В. Н. Каразіна, 2012)
This article has considered the features of the institute of probation and the possibi-lity of its use in Ukraine. The main attention is paid to the use of probation in different countries. The research has identified the main characteristics of the institute and the best options available to its introduction into Ukrainian law.
В этой статье рассмотрены особенности института пробации и возможности его использования в Украине. Основное внимание уделяется использованию пробации в разных странах. В ходе исследования были выявлены основные характеристики данного института и предоставлены оптимальные варианты его внедрения в украинское право.
Keywords: institute of probation; Ukrainian law